1988
DOI: 10.3109/10826088809058832
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of the Contribution Made by Irrational Beliefs and Parental Interaction to Adolescent Drug Abuse

Abstract: Using commonality analysis, a method of partitioning variance into shared and unique components, this study examined the relative importance of irrational beliefs and sets of family factors in predicting adolescent substance abuse. The data revealed both mothers' and fathers' child-rearing practices and adolescents' irrational beliefs to be independent predictors. Moreover, the constellation of child-rearing practices to emerge, which was reflective of achievement pressure and conditional approval, corresponde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…13,14 It is postulated that holding negative views about the world and the future and ruminating about negative events are linked to substance abuse tendencies. 37,38 Taken together, this study found a higher prevalence of all distal to proximal dysfunctional cognitions in ADG. This suggests that all the elements of cognitions such as EMS, which is the most fundamental and rigid cognitive structure, a dysfunctional attitude, which is the reflection of schemas, cognitive distortion, which continues to perpetuate schemas through its information processing mechanism, and negative automatic thought, which is the most superficial level of cognition, are all interconnected.…”
Section: Original Articlesupporting
confidence: 66%
“…13,14 It is postulated that holding negative views about the world and the future and ruminating about negative events are linked to substance abuse tendencies. 37,38 Taken together, this study found a higher prevalence of all distal to proximal dysfunctional cognitions in ADG. This suggests that all the elements of cognitions such as EMS, which is the most fundamental and rigid cognitive structure, a dysfunctional attitude, which is the reflection of schemas, cognitive distortion, which continues to perpetuate schemas through its information processing mechanism, and negative automatic thought, which is the most superficial level of cognition, are all interconnected.…”
Section: Original Articlesupporting
confidence: 66%
“…Although there were no differences between the conditions in terms of DAS changes, the CBT patients showed better improvements in self-efficacy, alcohol-related expectancies, and drinking outcomes. Denoff (1988) found that parental child rearing and a client's irrational beliefs were independent predictors of substance abuse among adolescents seeking residential treatment. Child-rearing practices related to achievement pressure, conditional approval, and avoidance of responsibility were particularly salient predictors.…”
Section: Schema-related Research In Substance Abuse Substance Use And...mentioning
confidence: 93%
“…29 Denoff showed that the cognitive and systemic factors of adolescents who abused drugs were significantly different from those who abstained from drugs. Studies have also shown that the group of addicts have significantly more inefficient attitudes, 30 As a result, it can be said that cognitive therapy appears necessary for these patients. Although cognitive interventions are mostly used in conjunction with behavioral techniques in the treatment of psychological problems and especially the phenomenon of addiction, however, the cognitive reconstruction approach, which is a tool in the cognitive therapy approach, has focused on recognizing and correcting and replacing defective perceptions and beliefs.…”
Section: Discussionmentioning
confidence: 99%